Understanding and Mitigating Stress among Hostelite Youth: A Comprehensive Review of Factors and Interventions - Akshat Jain; Rucha Akhani; Krrish Gupta; Dhruv Rankawat; Rahul Chauhan; Andino Maseleno (Greenation International Journal of Law and Social Sciences, 2023)
This study examines the factors influencing stress among hostelite youth, focusing on the impact of communal living on mental well-being, academic performance, and social adjustment. Through an analysis of various stressors, including homesickness, dissatisfaction with food quality, and strict hostel regulations, the research highlights the challenges faced by students in hostel environments. Using a quantitative approach, the study reveals age-based variations in stress perception, underscoring the need for tailored support strategies to enhance students' hostel experience. The findings suggest that effective interventions, such as improved counseling services, diverse meal options, and flexible management policies, can mitigate stress and support overall well-being. This study also emphasizes the global relevance of addressing hostelite stress, as these insights can inform best practices in student housing worldwide, contributing to improved academic and personal outcomes for students across borders.